The KNOWLEDGE LEVEL OF TRIMESTER III PREGNANT WOMAN ABOUT CONTRACEPTION INTRA UTERINE DEVISE POST PLASENTA AT BPM Bd. SATIMAH SAWANGAN DEPOK - Rosina Kardina Kidi Hurek (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2020)
Based on the BKKBN report in August 2012, only 7.46% of the 6,152,231 acceptors used the IUD. This shows that the IUD is still less desirable. In response to this, the government has launched the latest family planning program, namely the Post Placenta IUD. Post Placenta IUD is an IUD that is inserted after the placenta is born (± 10 minutes after the placenta is born). The advantage, apart from the more effective placement, because it is done after the placenta is born it also reduces the mother's morbidity. This study aims to describe the level of knowledge of third trimester pregnant women about Post Placenta IUD at BPM Bd. Satimah Sawangan Depok. This research is descriptive with data analysis using univariate. This research was conducted at BPM Bd.Satimah Sawangan Depok on 13-16 August 2015. The population in this study were 42 pregnant women TM III (May-June 2015 period). Sampling was carried out on a non-probability basis with an accidental sampling technique of 42 people. From the results of the study, it was concluded that of the 42 TM III pregnant women, the most were 34 people (81.0%), 32 people (76.2%) were not working, 25 were highly educated (59.5%), and Most of them obtained information from health workers / family / friends as many as 32 people (76.2%) and most of TM III pregnant women had less knowledge about Post Placenta IUD as many as 24 people (57.1%). Efforts are needed to promote health and counseling about the Post-placental IUD to increase knowledge so as to strengthen mothers to use long-term family planning. Keyword : WOMAN PREGNANT, IUD POST PLASENTA